The Important Role of MSMEs in National Economic Development - Handoko, A.D; Pramono, Nindyo; Siregar, Mahmul; Nasution, Mirza; Barus, Utary Maharany (Talenta Publisher, 2023)
ABSTRACT Member countries of the Organisation for Economic Co-operation and Development (OECD), make MSMEs a default factor in every economic law, especially investment law. However, the role of MSMEs in Indonesia is still often underestimated and has not received adequate opportunities to play their role in national economic development. The main problem in this research is to question how the issue of providing opportunities for the development of MSMEs in the rule of law in the economic sector in Indonesia. By using the normative juridical legal research method, it appears that MSMEs have an important role in national economic development, and therefore become an important target in efforts to achieve the State's Goal in promoting general welfare. The data collection technique in this study uses secondary data with qualitative data analysis techniques. From this research, it was found that there is an awareness of the importance of the role of MSMEs in national economic development, which is contained in various policies and legal regulations. The problem is that the implementation of these policies and regulations are still not in line with expectations. From the results of this research, it is recommended that the Government of Indonesia to reform the investment law in which it is mandated to provide opportunities for the development of MSMEs, so that MSMEs can really play an important role in the national economic development. Keywords : investment law, national economic development, role of MSMEs, legal reform;